The Influence of Price and Store Atmosphere on Purchasing Decisions: Study at a Bookstore in Bandung - Yusuf, Agung Muhammad; Supartini, Tini (P3M, STIE Pasundan, Bandung, Indonesia., 2025)
This study aims to investigate the impact of price and store ambiance on consumer purchasing decisions, using a case study of a bookstore located in Bandung. This study involved distributing questionnaires to a select group of respondents who were patrons of the bookstore. The researchers aimed to determine the extent to which pricing and store ambiance influence consumer purchasing decisions. This study employed a quantitative methodology utilising route analysis to investigate the direct and indirect interactions among variables. The findings demonstrate that price has a significant impact on purchasing decisions, both directly and indirectly through the store atmosphere variable. This condition indicates that when a bookstore's pricing aligns with buyers' expectations, the likelihood of purchase increases, particularly when complemented with a pleasant and appealing retail environment. The store atmosphere contributes significantly, albeit to a lesser extent than price. An orderly retail environment, adequate lighting, and appealing product displays can foster a favorable ambiance for consumers, thereby promoting purchases. Moreover, the analysis reveals that the interplay of pricing and store atmosphere characteristics may elucidate most purchasing decisions. These two characteristics greatly influence consumers' purchasing decisions at the bookshop selected for this study. Nonetheless, additional factors beyond these two variables also contribute, albeit to a lesser extent. Bookshop management should strike a balance between competitive pricing and creating a retail environment that enhances consumer comfort and satisfaction. This condition will help consumers make informed purchasing decisions and foster lasting loyalty.